2007
DOI: 10.3177/jnsv.53.324
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Prevents Oxidative Damage of High Glucose-Induced Cataractogenesis in Isolated Rat Lenses

Abstract: Summary Diabetic cataract is an ocular disease represented as blindness by lens opacification. Oxidative as well as osmotic stress caused by accumulation of polyols within the lens has been shown to be associated with glucose-induced cataractogenesis. Taurine has an antioxidant capacity and its level in diabetic cataractous lens is markedly decreased. Therefore, we investigated whether taurine is a part of antioxidative defense mechanism involved in protecting the lens against high glucose-induced oxidative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…A large number of studies and clinical applications demonstrated that Tau has many extensive physiological effects, so it was identified as an endogenous anti-injury material. Recently, Tau has been used as an antipyretic and anti-inflammatory agent, to treat liver and gallbladder disease [2], cardiovascular disease [3], diabetes [4,5], cataract [6,7], and so on. But its effect on tumors has not been previously studied.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies and clinical applications demonstrated that Tau has many extensive physiological effects, so it was identified as an endogenous anti-injury material. Recently, Tau has been used as an antipyretic and anti-inflammatory agent, to treat liver and gallbladder disease [2], cardiovascular disease [3], diabetes [4,5], cataract [6,7], and so on. But its effect on tumors has not been previously studied.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies and clinical applications demonstrated that Tau has extensive physiological effects, and has been identified to be the endogenous anti-injury material. Recently, Tau has been used to in the therapy of diseases, including liver and gallbladder disease (2), cardiovascular disease (3), diabetes (4,5) and cataract (6,7). However, studies on its effect on tumors remains limited and the mechanism of its antitumor ability is ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, taurine appeared to protect the lens against the development of sugar-induced cataracts and may have exerted this effect by decreasing oxidative damage (Malone et al, 1993;Rathore and Gupta, 2010). The role of taurine deficiency in cataract development has been studied by a number of other groups (Zhang and Chen, 1998;Son et al, 2007;Hsu et al, 2012). It is possible that the deficiency of taurine in the cubs receiving the two different artificial milk formulas may have exposed their lenses to an oxidative effect.…”
Section: Milk and Serum Analyses Resultsmentioning
confidence: 99%